2020
DOI: 10.1002/cyto.b.21881
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometric evaluation of TRBC1 expression in tissue specimens and body fluids is a novel and specific method for assessment of T‐cell clonality and diagnosis of T‐cell neoplasms

Abstract: Background: Flow cytometric detection of T-cell clonality is challenging. The current available methodology for T-cell receptor (TCR) Vβ repertoire evaluation is a complex assay and has limited sensitivity especially for detecting low levels of disease. Therefore, there is an unmet need for a reliable, simple, and rapid assay to identify T-cell clonality. The rearrangement of the TCRB gene involves the random and mutually exclusive expression of one of two constant β chain genes (TRBC1 and TRBC2), analogous to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
31
2
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 23 publications
(42 reference statements)
6
31
2
1
Order By: Relevance
“…All cases of mature T-cell lymphomas with documented neoplastic T-cell populations showed restricted (monotypic) TRBC1 expression, a sensitivity of 100%. We also established the expression patterns of TRBC1 in normal T-cell subsets from tissue and body fluid cases without a T-cell neoplasm, and we demonstrated that T-cell malignancies show a narrow and distinctly restricted (positive or negative) TRBC1 expression [81]. T-cell receptor gene rearrangement (TCR-PCR) studies were available in 38/46 (82.6%) of tissues or body fluids diagnosed with a T-cell neoplasm and in 8/97 (8.3%) of specimens without a T-cell malignancy.…”
Section: Applications Of Trbc1 Assessment For Tissue Analysis and Lowmentioning
confidence: 91%
See 1 more Smart Citation
“…All cases of mature T-cell lymphomas with documented neoplastic T-cell populations showed restricted (monotypic) TRBC1 expression, a sensitivity of 100%. We also established the expression patterns of TRBC1 in normal T-cell subsets from tissue and body fluid cases without a T-cell neoplasm, and we demonstrated that T-cell malignancies show a narrow and distinctly restricted (positive or negative) TRBC1 expression [81]. T-cell receptor gene rearrangement (TCR-PCR) studies were available in 38/46 (82.6%) of tissues or body fluids diagnosed with a T-cell neoplasm and in 8/97 (8.3%) of specimens without a T-cell malignancy.…”
Section: Applications Of Trbc1 Assessment For Tissue Analysis and Lowmentioning
confidence: 91%
“…We have recently expanded on our flow cytometric strategy to assess T-cell clonality using a single TRBC1 antibody (JOVI-1), to include tissue and body fluid specimens, in addition to peripheral blood and bone marrow samples [81]. Our evaluation of 143 tissue and body fluid specimens, comprising both patients with a definitive diagnosis of a T-cell neoplasm and patients with no T-cell malignancy, included a broad array of specimen types from multiple anatomic sites (lymph nodes, spleen, lung/mediastinum, tonsil, gastrointestinal/liver, nasopharynx, and soft tissue), as well as pleural, peritoneal, and cerebrospinal fluids.…”
Section: Applications Of Trbc1 Assessment For Tissue Analysis and Lowmentioning
confidence: 99%
“…In this issue of Cytometry B, Berg et al (2021) confirm and extend on previous observations in blood and bone marrow samples, (Novikov et al, 2019;Shi et al, 2020;Horna, Shi, Jevremovic et al, 2021;Horna, Shi, Olteanu et al, 2021) and demonstrate further the utility of assessing TRβC1 expression in combination with a panel of other conventional T-cell associated markers to assess T cell clonality in immunophenotypically defined subsets of mature T cells in tissue biopsies and other body fluids (e.g., CSF, pleural effusions and peritoneal fluid) (Berg et al, 2021). Based on their results on a series of 46 mature/peripheral T cell neoplasms and 97 patients with no T cell malignancy, they conclude that detection of T cell clonality in phenotypically defined subsets of T cells using the single TRβC1 antibody staining in tissue biopsies and distinct body fluids is a simple, fast and robust assay, which might be ready to be incorporated in routine diagnostic flow cytometry laboratories (Berg et al, 2021).…”
Section: Flow Cytometric Detection Of T-cell Clonality In the Diagnostic Work-up Of Mature/peripheral T-cell Neoplasms In Tissue Biopsiesmentioning
confidence: 98%
“…This, together with the low frequency of mature/peripheral T cell neoplasms, compared to B-cell leukemia/lymphoma and to a less extent also myeloid malignancies (Swerdlow et al, 2017), has hampered adoption of flow cytometric analysis of the TCRVβ repertoire for the diagnostic work-up of mature/peripheral T cell neoplasms in many laboratories worldwide. Recently, antibody reagents specific for the constant region 1 of the TCRβ chain (TRβC1) have been produced (Novikov et al, 2019) which have proven to be of great potential utility for rapid flow cytometry-based assessment of T-cell clonality (Novikov et al, 2019;Shi et al, 2020;Horna, Shi, Jevremovic et al, 2021;Horna, Olteanu, Jevremovic et al, 2021;Horna, Shi, Olteanu et al, 2021), in a similar way the pattern of expression of the immunoglobulin kappa vs lambda light chains are used for detection of B cell clonality. In this issue of Cytometry B, Berg et al (2021) confirm and extend on previous observations in blood and bone marrow samples, (Novikov et al, 2019;Shi et al, 2020;Horna, Shi, Jevremovic et al, 2021;Horna, Shi, Olteanu et al, 2021) and demonstrate further the utility of assessing TRβC1 expression in combination with a panel of other conventional T-cell associated markers to assess T cell clonality in immunophenotypically defined subsets of mature T cells in tissue biopsies and other body fluids (e.g., CSF, pleural effusions and peritoneal fluid) (Berg et al, 2021).…”
Section: Flow Cytometric Detection Of T-cell Clonality In the Diagnostic Work-up Of Mature/peripheral T-cell Neoplasms In Tissue Biopsiesmentioning
confidence: 99%
See 1 more Smart Citation